Fertile window and biophysical biomarkers of cervical secretion in subfertile cycles: a look at biotechnology applied to NaProTechnology - José María Murcia Lora; Oscar Martínez Martínez; Jennifer Simoni; Marian Martínez Calvo; Alberto Falces de Andrés; Jorge Enrique Mejía; Diglio Simoni; Juan Luis Alcázar (IMR Press, 2022)
Background: The principal objective of this study was to correlate biophysical properties of vaginal discharge present in the cervical mucus with the timing of the fertile window. In particular, we produce measures of the viscoelasticity of the cervical secretion using two methods. The first uses only the elasticity extracted from the Creighton Model Fertility Care System (CrMs) scale, calculated P-6 ovulation estimated day (OED) with respect to the peak day of the CrMs. The second uses a numerical method that takes into account the changes in viscoelasticity, but without reference to the peak day calculated using the CrMs model. Using both methods, twelve records were obtained from a single female subject. Methods: The methodology used to evaluate the viscoelasticity factor was by measuring the approximate length in centimeters (cm) of the vaginal discharge of cervical discharge. For this, the scale of the stretching graph established by observing the stretching of CrMS was used, taking into account the previous 6 days at peak day P-6. The first method, which we termed CFW (Clinical Fertile Window), uses a measure based on the approximate length (cm) of the maximal stretchiness of the vaginal discharge. The second method we termed SFW (Software-CrMS/strectching) (Software-based Fertile Window). Results: The fertile window was detected correctly in 100% of the cases using either method, and a correlation value of 0.71 was observed between the two methods. Conclusions: We conclude that the assessment of viscoelasticity using SFW algorithm allowed in this pilot study to detect the fertile window and to describe the evolution pattern of cervical discharge throughout the fertile window. Our study provides support for the use of computational methods in detecting the fertile window, taking only into account the time evolution of the cervical discharge throughout the menstrual cycle.